Higher Levels of Plasma Hyaluronic Acid and N-terminal Propeptide of Type III Procollagen Are Associated With Lower Kidney Function in Children With Non-alcoholic Fatty Liver Disease - Mosca, Antonella; Mantovani, Alessandro; Crudele, Annalisa; Panera, Nadia; Comparcola, Donatella; De Vito, Rita; Bianchi, Marzia; Byrne, Christopher D.; Targher, Giovanni; Alisi, Anna (Frontiers in Pediatrics, 2022)
Objective. Hyaluronic acid (HA) and N-terminal propeptide of type III procollagen (PIIINP) are two non-invasive biomarkers of liver fibrosis in non-alcoholic fatty liver disease (NAFLD). We examined the relationships of plasma levels of HA and PIIINP with kidney function in children with NAFLD. Methods. Plasma HA and PIIINP levels were measured using two commercially available enzyme-linked immunosorbent assay kits in a cohort of 106 Caucasian overweight or obese children with biopsy-proven NAFLD. Glomerular filtration rate (eGFR) was estimated using the Bedside Schwartz equation. Genotyping for the patatin-like phospholipase domain-containing protein-3 (PNPLA3) rs738409 variant was performed using an allelic discrimination assay. Results. Children with fibrosis F2 had significantly higher plasma PIIINP and HA levels than those with F0 or F1 fibrosis. Liver fibrosis was positively associated with plasma HA and PIIINP, as well as with the presence of the risk allele G of PNPLA3 rs738409 variant, and negatively with eGFR. Moreover, eGFR showed significant inverse associations with HA and PIIINP levels, as well as the presence of G of PNPLA3 rs738409, and liver fibrosis stage. Notably, our multivariable regression models showed that higher plasma PIIINP (standardized beta coefficient: -0.206, p=0.011) and HA levels (standardized beta coefficient: -0.531, p<0.0001) were associated with lower eGFR values, even after adjustment for age, sex, systolic blood pressure, PNPLA3 rs738409 genotype and any stage of liver fibrosis. Conclusions. Higher levels of HA and PIIINP were associated with lower eGFR values in Caucasian children with biopsy-proven NAFLD, independently of PNPLA3 rs738409 genotype and other potential confounding factors.